2015
DOI: 10.17140/lroj-1-104
|View full text |Cite
|
Sign up to set email alerts
|

Acute Liver Injury during Co-treatment with Levetiracetam and Temozolomide

Abstract: Citation ABSTRACTDrug-induced liver injury (DILI) accounts for approximately 10 percent of all cases of acute hepatitis. The patterns of acute injury include any form of hepatic injury, but the most common problems are cholestasis, hepatocellular damage, or a mixed type. DILI is often reversible, and discontinuation of the offending agent usually results in a complete recovery; however, some cases may lead to chronic liver injury, cirrhosis, and even death. Temozolomide (TMZ) is an alkylating, anti-neoplastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…These side effect could possibly increase or decreased with the use of generic forms of LEV. Although not previously known as a cause increasing hepatic enzymes, several recent case studies have reported elevation in liver enzymes associated with the utilization of LEV either as a monotherapy or in combination with other medications such as temozolomide or Lacosamid ( Broli et al, 2010 , Chen et al, 2015 , Gutiérrez-Grobe et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…These side effect could possibly increase or decreased with the use of generic forms of LEV. Although not previously known as a cause increasing hepatic enzymes, several recent case studies have reported elevation in liver enzymes associated with the utilization of LEV either as a monotherapy or in combination with other medications such as temozolomide or Lacosamid ( Broli et al, 2010 , Chen et al, 2015 , Gutiérrez-Grobe et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%